Migration and Canadian Interprovincial Trade - Nusrate Aziz; Ahmed Aziz; Gerry Mahar (Global Labor Organization (GLO), 2022)
This study estimates international and interprovincial migrants' impact on interprovincial trade using panel data from 1981- 2016 for Canadian provinces. Estimated results show that migration plays a significant role in determining Canadian interprovincial trade. Although the stock of interprovincial migrants is smaller than the stock of immigrants in Canadian provinces, the earlier plays a consistently positive and significant role in interprovincial trade, but the latter is not consistently significant across estimators. Trade openness, population-weighted distance, and language proximity are also significant factors of interprovincial trade creation. Our results are robust to different estimation methods, model specifications, and alternative measures of migrants' stock in Canadian provinces.
Keywords: C33; C36; F16; F22; 330; interprovincial migration; immigration; interprovincial trade; gravity model; IV approach